2014
DOI: 10.3109/00016357.2013.798872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cannibalistic cells: a novel entity in prediction of aggressive nature of oral squamous cell carcinoma

Abstract: Interestingly the cases with positive lymph node metastasis demonstrated Grade 3 CC.Hence, during routine histopathological examination, the search of CC can be considered as one of the important parameters to note the aggressive nature of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…CC has been frequently observed in vivo in seve ral benign and malignant tumors including breast carcinoma [8], giant cell carcinoma of lung [9], endometrial stromal sarcoma [10], malignant melanoma [11], gastric adenocarcinoma [12], giant-cell tumor of the tendon sheath [4], lung carcinoma, gall bladder carcinoma [13], giant cell granuloma of the oral cavity [14], salivary duct carcinoma [15], oral squamous cell carcinoma (OSCC) [16][17][18][19]. These tumor cells cannibalize their siblings as well as cells from the immune system in order to sustain and defend existing unfavorable conditions within the microenvironment such as hypoxia, lack of nutrition and acidity.…”
Section: Cellular Cannibalism and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…CC has been frequently observed in vivo in seve ral benign and malignant tumors including breast carcinoma [8], giant cell carcinoma of lung [9], endometrial stromal sarcoma [10], malignant melanoma [11], gastric adenocarcinoma [12], giant-cell tumor of the tendon sheath [4], lung carcinoma, gall bladder carcinoma [13], giant cell granuloma of the oral cavity [14], salivary duct carcinoma [15], oral squamous cell carcinoma (OSCC) [16][17][18][19]. These tumor cells cannibalize their siblings as well as cells from the immune system in order to sustain and defend existing unfavorable conditions within the microenvironment such as hypoxia, lack of nutrition and acidity.…”
Section: Cellular Cannibalism and Cancermentioning
confidence: 99%
“…Jose et al [18] evaluated 20 neck dissection cases of OSCC and found statistically significant correlation between advanced grade of CC and positive lymph node metastasis. So, the authors concluded that CC can be considered as one of the important parameter to assess an aggressive nature of OSCC.…”
Section: Cellular Cannibalism As a Prognosticator Of Oral Squamous Cementioning
confidence: 99%
“…Various methodologies have been used for grading EK in various tumors. Especially in OSCC, Jose et al 13 The EK ranged from 1 to 10 with mean of 4.125 + 2.107. The phenomenon of complex endocytosis was observed in 9 (16.07%) cases.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, for the management of a lesion, histopathologic parameters must be considered in hematoxylin and eosin staining of specimens, and more attention must be paid to cellular and histological aspects. 3 CC is among these parameters, and can be observed under a light microscope without requiring any advanced molecular technique. 1,3,4 The presence of CC has not been previously reported in LP.…”
mentioning
confidence: 99%
“…3 CC is among these parameters, and can be observed under a light microscope without requiring any advanced molecular technique. 1,3,4 The presence of CC has not been previously reported in LP. However, it can be identified in LP specimens with careful inspection (Figure 1…”
mentioning
confidence: 99%